The technology of organization of admittance controls of a single stage of flight of aircraft owing to the data of on-board parametrical registers - Малежик, О.І.; Радченко, В.А.; Куклінський, М.В. (Proceedings of National Aviation University (archive), 2005)
The article includes the researches on main principles of design of algorithmics and software for control of unsafe deviations on a single stage of flight of aircraft owing to the data of onboard parametrical registers.